Comparison of lesser toe proximal interphalangeal joint arthrodesis versus resection arthroplasty: a randomized controlled study - Scheidt, Sebastian; Nowak, Victoria; Mittag, Falk; Götze, Marco; Wülker, Nikolaus; Hofmann, Ulf Krister (Orthopedics, 2022)
The goal of this study was to compare operative outcomes after lesser toe deformity correction with either proximal interphalangeal (PIP) joint arthrodesis or PIP joint resection arthroplasty. A prospective randomized controlled trial was performed with 37 patients (48 toes) operated on with one of these two procedures. Evaluation of the numeric rating scale score, the American Orthopedic Foot and Ankle Society score, osseous consolidation, and clinical outcome was performed preoperatively and at 6 weeks and 6 months postoperatively. Both study groups showed significant improvement at 6 months postoperatively. Although osseous consolidation was significantly higher for the arthrodesis group (P=.001), this difference did not affect clinical outcomes, and at 6 months postoperatively, pain on the numeric rating scale was 0 (range, 0–7) for the arthroplasty group and 0 (range, 0–5) for the arthrodesis group (P=.669). The American Orthopedic Foot and Ankle Society score was 83 (range, 39–95) and 80 (range, 59–95), respectively (P=.879). No difference was observed for signs of inflammation or axis correction. Even a direct comparison of toes with radiologically osseous fusion (n=16) with those without fusion (n=32) did not show any clinical differences. This randomized controlled study showed no clinical differences in outcome between PIP joint arthrodesis and PIP joint resection arthroplasty for correction of lesser toe deformities, with good to excellent outcomes for both groups.